The Eastward Transmission of Augustine’s Eschatology in Ming and Qing China (宗教与历史 （ISSN: 3068-4803）, 2025)
Augustine’s eschatological doctrines were highly regarded during the Middle Ages and saw a revival in the early modern period. During the Ming and Qing dynasties, Catholic missionaries arrived in China and compiled relevant works, spreading Augustine’s eschatological thoughts through quotations. This paper provides a detailed introduction to the writings related to Augustine’s eschatological ideas by missionaries such as Diego de Pantoja, Alphonse Vagnoni, Philippe Couplet, Manuel Dias, Thomás Ortiz, as well as the Chinese catholic scholars Zhang Xingyao and Li Wenyu. Additionally, it discusses Gabriel de Magalhães’s translation of Fuhuo lun from the Thomas Aquinas’s Summa Theologiae. This paper argues that Augustine’s eschatological ideas are well represented in Chinese documents from the Ming and Qing dynasties. The frequency of quotations regarding his eschatology is comparable to that of his views on the Trinity and the Imago Dei, underscoring the significance of his theory of human nature and thoughts on humanity’s ultimate destiny in the context of Ming and Qing China.